Equalisation of territorial units' incomes - case study of Nordic, Central European and Southern countries - Maciej Turala; Lasse Oulasvirta; Yannis Psycharis; Gertrudes Guereiro; Gabor Peteri; Pontus Talberg (European Regional Science Association (ERSA), 2014)
Countries chosen for comparison within the framework of this paper are different in terms of geographical location, size, levels of socio-economic development and adopted local government systems. The major criterion for choosing case study countries was their geographical location, as it is the authors' intention to highlight differences in approach to fiscal equalisation between the Nordic countries (Finland and Sweden), Central European countries (Poland and Hungary), and the Mediterranean countries (Greece and Portugal). The hypothesis which is put forward and tested by the research team is as follows: The attitudes and approaches towards fiscal equalisation between local governments in: (1) the Nordic countries, (2) the Central European countries and (3) the Mediterranean countries differ significantly, reflecting cultural differences and different economic conditions in these countries. Specifically, the following sub-hypotheses are put forward and tested: + higher level of socio-economic development tends to favour stronger equalisation policy and mechanisms between local governments; + countries where local governments participate to a greater degree in public sector expenditures require far stronger equalisation mechanisms. The paper starts with snap-shot descriptions of countries chosen for analysis. Country backgrounds present situation in terms of socio-economic development, inequality in terms of personal wealth distribution and approaches to equalisation of personal incomes in respective countries. Each country's background also includes basic information on administrative division, scope of tasks performed by local governments, general structure of local government incomes and level of local government expenditure relative to GDP or central government spending. The second part of the paper is devoted to describing in more detail the grant systems and income equalisation mechanisms applied in all six case study countries. The final, third, part of the paper presents examples of how equalising measures work in relation to selected local governments which provide an overview of local governments of different income level prior to equalisation. This part then leads to conclusions, revisiting the hypotheses formulated above. The conclusions described in the paper are of a tentative character, showing possible research problems for future in-depth analyses which were not possible in a large, six-country comparison.
Keywords: 330